Composite steel and concrete structural members : fundamental behaviour - Oehlers, Deric J. (Pergamon, 1995)
This book deals with the analysis and behaviour of composite structural members that are made by joining a steel component to a concrete component. The emphasis of the book is to impart a fundamental understanding of how composite structures work, so engineers develop a feel for the behaviour of the structure, often missing when design is based solely by using codes of practice or by the direct application of prescribed equations. It is not the object to provide quick design procedures for composite members, as these are more than adequately covered by recourse to such aids as safe load tables. The subject should therefore be of interest to practising engineers, particularly if they are involved in the design of non-standard or unusual composite structures for buildings and bridges, or are involved in assessing, upgrading, strengthening or repairing existing composite structures. The fundamentals in composite construction are covered first, followed by more advanced topics that include: behaviour of mechanical and rib shear connectors; local buckling; beams with few shear connectors; moment redistribution and lateral-distortional buckling in continuous beams; longitudinal splitting; composite beams with service ducts; composite profiled beams and profiled slabs; composite columns; and the fatigue design and assessment of composite bridge beams.